2010
DOI: 10.1097/ico.0b013e3181ba7016
|View full text |Cite
|
Sign up to set email alerts
|

Dissection Plane in Deep Anterior Lamellar Keratoplasty Using the Big-Bubble Technique

Abstract: Dissection plane in DALK using the big-bubble technique can be within corneal stroma rather than exactly between stroma and DM. Various corneal pathologies as well as different techniques of dissection may have influence on this level.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

3
20
0

Year Published

2011
2011
2023
2023

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 48 publications
(23 citation statements)
references
References 24 publications
3
20
0
Order By: Relevance
“…First, our findings corroborate those of Jafarinasab et al ,4 with residual stroma in both studies being of a similar range: 2.6–17.4 μm in our study and 6.4–25.8 μm in their study. Second, if a stromal-DM dissection plane does occur routinely in the white-margin big-bubble in vivo, we would have expected to see it at least once in 30 samples.…”
Section: Discussionsupporting
confidence: 93%
See 1 more Smart Citation
“…First, our findings corroborate those of Jafarinasab et al ,4 with residual stroma in both studies being of a similar range: 2.6–17.4 μm in our study and 6.4–25.8 μm in their study. Second, if a stromal-DM dissection plane does occur routinely in the white-margin big-bubble in vivo, we would have expected to see it at least once in 30 samples.…”
Section: Discussionsupporting
confidence: 93%
“…Recently, a study examined three keratoconic eyes that underwent big-bubble DALK and required intraoperative conversion to penetrating keratoplasty 4. Histological examination found that all three eyes had a residual stromal layer covering the excised DM.…”
Section: Introductionmentioning
confidence: 99%
“…In our study, there was no evidence of splitting of DM, which is also in agreement with the findings of Saw et al 14 in keratoconus patient corneas. However, even in the presence of a big bubble, there were obvious residual stromal fibrils attached to DM; both of these histopathologic findings are similar to those reported by Jafarinasab et al 18 It should be noted that our outcomes are mainly based on a laboratory model for DALK with limited clinical results. Therefore, further comparative clinical studies are needed to evaluate and corroborate our findings.…”
Section: Discussionsupporting
confidence: 89%
“…However, a recent study of 3 big-bubble DALK converted intraoperatively to PK showed residual stroma remaining on DM in the posterior lamella of all 3 cases, the stromal thickness ranging from 6.4 to 25.8 mm. 10 Another study of excised stroma in 4 cases of manual dissection DALK showed residual DM on the excised stroma in 2 cases with the authors concluding that intrastromal and intra-DM cleavage planes may be more likely than a plane between stroma and DM. 11 We are currently investigating this further in another study.…”
Section: Discussionmentioning
confidence: 96%